The Types of Presupposition in the Jakarta Post's Education Articles - Zuka Cristyananda Mei Dewanta; Dina Sri Utami (International Consortium of Education and Culture Research Studies, 2020)
A speaker’s or writer’s presupposition shows a prejudice about a conversation opponent or someone being discussed. In this research, a presupposition analysis was conducted to provide information about the assumptions made by the Minister of Education and Culture Nadiem Makarim on various occasions in his speech to state his programs. It also aims to provide information to the reader that the intention conveyed by the speaker is precise and clear. Therefore, the authors declare in the various utterances that are delivered and explain the purposes. The data was taken randomly from the Jakarta Post online article about Education for a vulnerable period of one month from November 2, 2019, to December 2, 2019. This study used descriptive qualitative methods in answering questions in the problem statement; they are the explanation about what assumptions are often used by the Minister of Education and Culture and also explain the reasons for the use of these assumptions repeatedly. The assumptions found are lexical, non-factive, and counterfactual presupposition. Assumptions that are often used that aim that the use of certain expressions by the speaker is taken to presuppose other concepts (not stated), the use of certain expressions is made to presuppose the truth of the information said afterward.